Evaluation of dose calculation accuracy of treatment planning systems in the presence of tissue heterogeneities - Chopra, Kashmiri L.; Leo, Paul; Kabat, Christopher; Rai, Durg Vijay; Avadhani, Jaiteerth S.; Kehwar, Than Singh; Sethi, Anil (Therapeutic Radiology and Oncology, 2018)
Background: Accuracy of five dose calculation algorithms within three treatment planning systems (TPS): BrainLAB iPlan 4.2 (BL: pencil beam and Monte Carlo), Philips Pinnacle (PL: Collapsed Cone Calculation, CCC), and Varian Eclipse (VR: AAA and Acuros XB) is investigated in this multi-institutional study. Methods: A Monte-Carlo based TPS (BL) was first validated against benchmark measurements in heterogeneous-slab phantoms consisting of tissue-equivalent plastic, lung-equivalent cork, and bone density materials. Ion chamber/EDR film measurements of depth-dose and dose-profiles for 6MV enface photons in a range of field-sizes (12 mm × 12 mm – 60 mm × 60 mm) were performed. A common CT dataset for each phantom was sent to four participating institutions. Measured versus calculated dose differences for all dose algorithms considered in this study were quantified using two dose-profile indices: Ddiff within the central 80% of photon field, and Dspill for dose outside the field-edge (50–10% dose). Results: BrainLAB TPS BL: MC and measured doses agreed well (Ddiff